Identification of Potential Natural Bioactive Compounds from Glycyrrhiza glabra as Sars-CoV-2 Main Protease (MPRO) Inhibitors: In-Silico Approach - Abdusalam, Ashraf A. A.; Ben-Hander, Gazala M. (Al-Mukhtar Journal of Sciences, 2022)
The SARS-CoV-2 virus caused the COVID-19 pandemic declared in early 2020, generating a global health emergency. So far, no approved drugs or vaccines are available. Therefore, there is an urgent need to explore and develop effective new therapeutics against SARS-CoV-2. In addition, the main protease (Mpro) of the SARS-CoV-2 virus is considered essential in the virus replication propagation and considered a drug discovery target. Consequently, plant-derived compounds are an important and valuable source for novel drugs. This study reports molecular docking-based virtual screening (VS) of 20 compounds identified from Glycyrrhiza glabra to search for potent compounds against 3CL proteases (3CLpro). The screening results revealed that the identified compounds Semilicoisoflavone B, Licoflavone B, and Licocoumarin A exhibited low free energy of binding (FEB) values of 10.91, −10.29, and −10.21 kcal/mole for Autodock 4.2 and −9.81, −9.77, and −9.60 kcal/mole, for AutoDockVina, respectively. The obtained results of FEB in this study were better than the coordinated ligand N3, which was -7.4 kcal/mole. The three potential compounds showed different and stable interactions with the essential amino acids, especially the catalytic dyad (Cys145-His41) in the binding pocket of the 3CLpro. Three potential inhibitors were successfully identified from Glycyrrhiza glabra using molecular docking and virtual screening; these compounds obeyed the Lipinski rule of 5 with a little violation and showed low FEB and good interactions with the 3CLpro. These identified compounds may serve as potential leads that help in developing therapeutic agents against the SARS-CoV-2. Further research is recommended (in vitro and in vivo) to verify the above findings.